Telehealth Use during COVID-19: An Exploratory Study on Adaptations and Experiences of Providers. - DeHart, Dana; Iachini, Aidyn L; Browne, Teri; Reitmeier, Melissa; King, L Bailey (Health & Social Work, 2024)
The current exploratory study examines the impact of the rapid acceleration of telehealth during the COVID-19 pandemic from the perspective of healthcare providers. Understanding provider perspectives, particularly in terms of adaptations made during this critical time, is a useful lens into service innovation in times of crisis and can help elucidate successful strategies for continuing the use of telehealth during the postpandemic period. Fourteen providers from 11 different service agencies in a southeastern state were interviewed. Findings identified three themes: (1) dynamic adaptations enacted by healthcare providers at the onset of the pandemic, such as hybrid services, rapid innovations in workflow, collective decision making among providers, and outreach to educate patients; (2) the relaxation of policies by regulators/insurers, focused most often on reimbursement of services; and (3) how patient engagement was impacted via telehealth, including openness to telehealth, more family-level accessibility, and reduced no-show rates. Implications for social workers include heightened professional training on telehealth as well as increasing the critical role that social workers serve in educating providers and patients on telehealth.